ESTADO EMOCIONAL MATERNO E SUPORTE SOCIAL NA SÍNDROME DO X FRÁGIL - Franco, Vitor (2013)
The Fragile X Syndrome is a rare developmental disorder, generally underdiagnosed, despite being the more frequent inherited cause of cognitive impairment and the best known genetic origin for autism. We also know little about how fathers and mothers of children with FXS live their expe- rience given the presence of the disease, especially since such experience depends directly on the social and cultural context in which it takes place. The main objective of this work is to contribute to the recognition of the implications of having a child with FXS in the life history of mothers, in particular the impact on their emotional state and the value of social support. A case study methodology was used, with the mother of a teenager living in a rural setting in southern Portugal. The results indicate: a) the possibility of identifying the most significant moments and periods according with the school trajectory and the effective diagnosis, b) changes in mother’s emotional state resulting from these moments and c) weak social support facing the expressed emotional needs.